Internalisasi Nilai-nilai Islam dalam Praktik Ritual untuk Membentuk Karakter Siswa : Internalization of Islamic Values in Ritual Practice to Form Student Character - Sri Mulyani Maisaro; Sa’diyah Sa’diyah (Global Education Journal, 2026)
Internalization of Islamic values ​​through ritual practice in elementary schools is an important strategy in shaping students' character sustainably. This study aims to analyze four main aspects, namely the transformation, transaction, and transinternalization stages of Islamic values ​​in ritual practice, as well as the results of this internalization on the formation of student character at Al-Ummah Integrated Islamic Elementary School, Ciputat, South Tangerang. This study uses a qualitative approach with a descriptive method that aims to deeply understand the phenomenon of internalization of Islamic values ​​through religious activities in schools. Data analysis was carried out using the Milles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that 1) The value transformation stage, providing verbal understanding of the meaning of worship. 2) The value transaction stage, two-way interaction through worship practices and direct guidance. 3) The value transinternalization stage, teacher role models and behavioral consistency until the values ​​are integrated within the students. 4) The results of internalization are seen in the formation of religious character, increased discipline and responsibility, the development of noble morals, and the growth of social awareness and positive behavior in students' daily lives.